The Role of Customer Engagement Strategy and Quantitative Invesment Analysis: Sustainable MSMEs - Rustomo Rustomo; Ade Irawan (Politeknik Ganesha Medan, 2026)
This study is a follow-up study on street vendors (PKL) on Jalan Pendidikan Mangunjaya Tambun and Perumas Tiga Kota Bekasi in 2022. They are still motivated to become sustainable micro, small, and medium enterprises (MSMEs). The purpose of this study is to analyze plans designed to build sustainable business relationships between street vendors and customers through various interactions. This creates customer loyalty, builds brand advocacy to create long-term value, or becomes an MSME. The research method is quantitative with a Quantitative Investment Analysis approach to analyze the relationship between factors in operational variables. The sampling technique is purposive sampling with a total of 6 (six) street vendors. Data collection uses a Likert scale questionnaire. Data analysis uses regression to analyze the strength of the relationship between variables and sub-variables. The results of the study show that the role of Customer Engagement Strategy and Quantitative Investment Analysis: Sustainable MSMEs partially affects Customer Engagement Strategy for Sustainable MSMEs from 5 (five) factors, 4 (four) factors are declared strongly positive and significant, and 1 (one) factor is declared moderately positive and insignificant. Capital on sustainable MSMEs from 3 (three) factors was declared to be very strong and significant overall. In the simultaneous results, Customer Engagement Strategy and capital on sustainable MSMEs were strong and significant.